Aging-Related Defects Are Associated With Adverse Cardiac Remodeling in a Mouse Model of Reperfused Myocardial Infarction - Bujak, Marcin (2008)
OBJECTIVES: The purpose of this study was to study aging-associated alterations in the inflammatory and reparative response after myocardial infarction (MI) and their involvement in adverse post-infarction remodeling of the senescent heart. BACKGROUND: Advanced age is a predictor of death and ventricular dilation in patients with MI; however, the cellular mechanisms responsible for increased remodeling of the infarcted senescent heart remain poorly understood. METHODS: Histomorphometric, molecular, and echocardiographic end points were compared between young and senescent mice undergoing reperfused infarction protocols. The response of young and senescent mouse cardiac fibroblasts to transforming growth factor (TGF)-β stimulation was examined. RESULTS: Senescence was associated with decreased and delayed neutrophil and macrophage infiltration, markedly reduced cytokine and chemokine expression in the infarcted myocardium, and impaired phagocytosis of dead cardiomyocytes. Reduced inflammation in senescent mouse infarcts was followed by decreased myofibroblast density and markedly diminished collagen deposition in the scar. The healing defects in senescent animals were associated with enhanced dilative and hypertrophic remodeling and worse systolic dysfunction. Fibroblasts isolated from senescent mouse hearts showed a blunted response to TGF-β1. CONCLUSIONS: Although young mice exhibit a robust post-infarction inflammatory response and form dense collagenous scars, senescent mice show suppressed inflammation, delayed granulation tissue formation, and markedly reduced collagen deposition. These defects might contribute to adverse remodeling. These observations suggest that caution is necessary when attempting to therapeutically target the post-infarction inflammatory response in patients with reperfused MI. The injurious potential of inflammatory mediators might have been overstated, owing to extrapolation of experimental findings from young animals to older human patients.